2004
DOI: 10.1207/s15327914nc5002_8
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene Supplementation Prevents the Development of Spontaneous Smooth Muscle Tumors of the Oviduct in Japanese Quail

Abstract: Leiomyomas (fibroids) are benign tumors of the uterus affecting millions of women. Spontaneous leiomyomas of the oviduct are common tumors of the Japanese quail (Coturnix coturnix japonica), which makes it a good animal model for screening potential agents for testing in the prevention and treatment of human myoma uteri. Because dietary intake of lycopene has been associated with a reduced risk of a variety of human cancers, we investigated the effects of lycopene supplementation on the development of leiomyom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 61 publications
5
22
0
Order By: Relevance
“…Similar to our results, Jain et al (1999) reported that dietary lycopene decreased serum TBA reactive substances (14% reduction) concentration in rats. Sahin et al (2004Sahin et al ( , 2006a reported that quail supplemented with pure lycopene had a significant reduction in MDA values in serum and liver.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our results, Jain et al (1999) reported that dietary lycopene decreased serum TBA reactive substances (14% reduction) concentration in rats. Sahin et al (2004Sahin et al ( , 2006a reported that quail supplemented with pure lycopene had a significant reduction in MDA values in serum and liver.…”
Section: Discussionmentioning
confidence: 99%
“…One study in Japanese quail demonstrated that supplementation with lycopene reduces the incidence of leiomyoma in these animals (9). However, lycopene action in an animal model may not accurately represent lycopene action in humans.…”
Section: Commentmentioning
confidence: 99%
“…The administration of a lycopene supplement to quail results in reduced number and size of leiomyoma in the oviduct compared to quail who did not receive the lycopene supplement (9). To our knowledge, the relation between carotenoids and UL has not been investigated in humans.…”
Section: Introductionmentioning
confidence: 96%
“…However, in our previous in vivo study in Japanese quail model we observed that lycopene could inhibit the formation of fibroid tumors in a dosedependent manner [25]. Tang et al [28] suggested that lycopene could act as a chemopreventive agent against the growth and progression of colorectal cancer in a mouse xenograft model.…”
Section: Discussionmentioning
confidence: 92%
“…The rats were fed either a basal diet or the basal diet supplemented with either 100 or 200 mg lycopene per kilogram of diet. The dose of lycopene was chosen based on our previous studies in the Japanese quail model [25]. Lycopene supplement was provided by DSM Nutritional Products Ltd, Switzerland, a 10% pure lycopene product.…”
Section: Animals and Experimental Designmentioning
confidence: 99%